2020
DOI: 10.3390/f11121285
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emissions from Oil Palm Induced Forest and Peatland Conversion in Sabah and Sarawak, Malaysia

Abstract: The palm oil industry is one of the major producers of vegetable oil in the tropics. Palm oil is used extensively for the manufacture of a wide variety of products and its production is increasing by around 9% every year, prompted largely by the expanding biofuel markets. The rise in annual demand for biofuels and vegetable oil from importer countries has caused a dramatic increase in the conversion of forests and peatlands into oil palm plantations in Malaysia. This study assessed the area of forests and peat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Indonesia and Malaysia as the two largest oil-palmproducing countries, might encounter similar situation over their peatland due to the expansion of oil palm plantation. The Government of Malaysia decided to limit the oil palm plantation in their country by up to 6.5 million ha in 2023 to prevent further deforestation and conversion of peatland into oil palm plantations, as well as to reduce CO2 emissions [9]. For a better management of oil palm in peatland, this land swap option with some adjustment will potentially be adopted by the Malaysian government.…”
Section: Land Swap Optionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia and Malaysia as the two largest oil-palmproducing countries, might encounter similar situation over their peatland due to the expansion of oil palm plantation. The Government of Malaysia decided to limit the oil palm plantation in their country by up to 6.5 million ha in 2023 to prevent further deforestation and conversion of peatland into oil palm plantations, as well as to reduce CO2 emissions [9]. For a better management of oil palm in peatland, this land swap option with some adjustment will potentially be adopted by the Malaysian government.…”
Section: Land Swap Optionmentioning
confidence: 99%
“…Malaysia, as the second largest producer of oil palm, might encounter similar issue on the management of oil palm in peatland. A study has shown that oil the palm plantation in a peatland in Sarawak, Malaysia has grown rapidly from 197,323 ha in 1990 to 657,273 ha in 2018 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its remarkable contribution to the economy, there has not been much progress in yield improvement in the last four decades as the CPO in a recent production of 3.16 t/ha/year in 2021 ( Parveez et al., 2022 ). With the current planted area of 5.74 million hectares and mature palms covering 89.7% ( Parveez et al., 2022 ), close to reaching the targeted limit of 6.5 million hectares introduced by the Malaysian government in committing to sustainability ( Wan Mohd Jaafar et al., 2020 ), extensive efforts are still being carried out to sustain and improve the higher productivity of the industry. Therefore, with limited land for replanting, increasing yield per unit of the land area is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, oil palm expansion is driving deforestation in Southeast Asia (Henderson and Osborne 2000; Koh and Wilcove 2007; Palm 2005). For example, in Malaysian Borneo, from 1990 to 2018, oil palm was responsible for decreasing the area of primary forest by 13% in Sarawk and 16% in Sabah and decreasing the area of peat forests from by 21% in Sarawak and 19% in Sabah (Jaafar et al 2020).…”
Section: Introductionmentioning
confidence: 99%